Immobilization Decreases FOXO3a Phosphorylation and Increases Autophagy-Related Gene and Protein Expression in Human Skeletal Muscle - Møller, Andreas Buch; Vendelbo, Mikkel Holm; Schjerling, Peter; Couppé, Christian; Møller, Niels; Kjær, Michael; Hansen, Mette; Jessen, Niels (Frontiers in Physiology, 2019)
Immobilization of the lower limbs promotes a catabolic state that reduces muscle mass, whereas physical training promotes an anabolic state that increases muscle mass. Understanding the molecular mechanisms underlying this is of clinical interest, as loss of muscle mass is a major complication to critical illness in humans. To determine the molecular regulation of protein synthesis and degradation during muscle loss and hypertrophy, we examined skeletal muscle biopsies from healthy human subjects after 2 weeks unilateral immobilization of a lower limb and during 6 weeks of physical rehabilitation. We have previously shown that cross-sectional area of the knee muscle-extensors decreased by 10% during immobilization and was completely restored during rehabilitation. Here we provide novel data to suggest that autophagy is an important underlying mechanism involved in regulation of muscle mass. Protein expression of MuRF1 and ATROGIN-1 did not change during the study, indicating that the recruitment of substrates to the proteasomes was unaltered. Phosphorylation of mTORat Ser2448 did not change during the study, and neither did phosphorylation of the mTORC1 substrates 4EBP1 Thr37/46 and p70S6K Thr389, suggesting that this pathway does not suppress protein synthesis during muscle wasting. Protein levels of p62 and ULK1 increased during immobilization and returned to baseline levels during rehabilitation. Same pattern was observed for FOXO3a phosphorylation at Ser318/321, suggesting transcriptional activation during immobilization and inactivation during rehabilitation. To investigate this further, we analyzed mRNA expression of seven autophagy-related genes controlled by FOXO3a. Five of these (p62, LC3B, BECLIN-1, ATG12, and BNIP3) increased during immobilization and returned to baseline during rehabilitation. In conclusion, immobilization of a lower limb increases autophagy-related gene and protein expression in human skeletal muscle in a pattern that mirrors FOXO3a phosphorylation. These findings could imply that FOXO3a dependent transcriptional regulation of autophagy is involved in the regulation of muscle mass in humans.